REMOTE-CONTROL MEASUREMENT SYSTEM BASED ON THE IEEE-488 - Cesak, Petr; Roztocil, Jaroslav (International Journal of Computing, 2014)
The paper presents a complete system for remote measurement. The system is based on the client-server communication structure over the Internet. One part considers the client application – it is used by a user to control the measurement. Second part deals with the server – the server application itself and local connection the instruments over the IEEE-488 interface bus. The communication between client and server is built on TCP connection.